All-solid-state potassium ion selective electrode and manufacturing method thereof

By using embedded materials containing Prussian blue analog particles and potassium ion sensing films in potassium ion selective electrodes, the problem of insufficient stability of existing potassium ion selective electrodes is solved, and higher stability and response sensitivity are achieved.

CN119678038APending Publication Date: 2025-03-21KOA CORP +1

Patent Information

Application Number
CN202380058712.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-25
Filing Date
2023-06-28
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The stability of existing potassium ion selective electrodes needs to be improved.

Method used

An all-solid potassium ion selective electrode is employed, which includes a conductor, an intercalating material formed on the surface of the conductor, and a potassium ion sensing film covering the intercalating material. The embedded material is a mixed material containing Prussian blue analog particles and conductive material particles. It forms a stable potassium ion sensing film by a specific manufacturing method such as immersion in aqueous potassium chloride solution and drying steps.

Benefits of technology

The stability of potassium ion selective electrodes is improved, ensuring long-term electrode performance maintenance, and enhancing the response sensitivity and detection limit to potassium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119678038A_ABST
    Figure CN119678038A_ABST
Patent Text Reader

Abstract

Provided are a potassium ion-selective electrode having higher stability and a method for manufacturing the same. The all-solid-state potassium ion selective electrode comprises a conductor; the embedded material is formed on the surface of the conductor; and a potassium ion sensing film covering the embedded material. The embedded material is a mixed material containing Prussian blue analogue particles and conductive material particles, the Prussian blue analogue particles are represented by a structural formula KxFe [Fe (CN) 6] y.nH2O, the Prussian blue analogue particles at least partially have a monoclinic crystal structure, x is a number greater than or equal to 1.5 and less than or equal to 2, y is a number greater than 0 and less than or equal to 1, and n is an integer greater than or equal to 1. N is a number greater than or equal to 0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an all-solid-state potassium ion selective electrode and a method for manufacturing the same. Background Art

[0002] Ion-selective electrodes respond to specific ions by generating a change in potential and are used in devices such as measuring ion concentration in liquids. Ion-selective electrodes are widely used in various fields such as environmental-related technologies, medical-related technologies, and agricultural-related technologies.

[0003] Ion selective electrodes that sense various ions are currently known. Patent Document 1 discloses a magnesium ion selective electrode and a calcium ion selective electrode containing a Prussian blue analog.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: JP2020046364 Summary of the invention

[0007] Problems to be solved by the present invention

[0008] However, the potassium ion selective electrode in the prior art has the problem of stability which needs to be improved.

[0009] The present invention aims to solve this problem, and its purpose is to provide a potassium ion selective electrode with high stability and a method for manufacturing the same.

[0010] Problem Solving Methods

[0011] In one example, the all-solid-state potassium ion selective electrode of the present invention comprises:

[0012] conductor;

[0013] an embedded material formed on a surface of the conductor; and

[0014] a potassium ion sensing membrane covering the embedding material,

[0015] Wherein, the embedding material is a mixed material containing Prussian blue analog particles and conductive material particles,

[0016] The Prussian blue analog particles have a structural formula K x Fe[Fe(CN)6] y nH2O means,

[0017] The Prussian blue analog particles at least partially have a monoclinic crystal structure,

[0018] x is a number greater than or equal to 1.5 and less than or equal to 2, y is a number greater than 0 and less than or equal to 1, and n is a number greater than or equal to 0.

[0019] In one example, in the method for manufacturing an all-solid-state potassium ion selective electrode of the present invention, the all-solid-state potassium ion selective electrode comprises:

[0020] conductor;

[0021] an embedded material formed on a surface of the conductor; and

[0022] a potassium ion sensing membrane covering the embedding material,

[0023] Wherein, the embedding material is a mixed material containing Prussian blue analog particles and conductive material particles,

[0024] The Prussian blue analog particles have a structural formula K x Fe[Fe(CN)6] y nH2O means,

[0025] The Prussian blue analog particles at least partially have a monoclinic crystal structure,

[0026] x is a number greater than or equal to 1.5 and less than or equal to 2, y is a number greater than 0 and less than or equal to 1, n is a number greater than or equal to 0,

[0027] The method comprises the following steps:

[0028] providing a slurry on a conductor, and drying the slurry to form a blended film on the surface of the conductor;

[0029] Immersing the blended film in a first potassium chloride aqueous solution so that K+ is evenly distributed in the Prussian blue analogue, thereby forming an embedded material on the conductor surface;

[0030] Providing a potassium ion sensing membrane mother solution on the surface of the embedding material, and drying the potassium ion sensing membrane mother solution to form an ion responsive mother membrane on the surface of the embedding material; and

[0031] The potassium ion sensing membrane is formed on the surface of the embedding material by immersing the ion responsive mother membrane in a second potassium chloride aqueous solution.

[0032] In one example, the method comprises the steps of preparing the slurry,

[0033] The slurry preparation step includes the step of synthesizing Prussian blue analog particles at least partially including a cubic crystal structure by oxidizing a monoclinic Prussian blue analog.

[0034] In one example, after the step of forming the potassium ion sensitive membrane, the method includes the step of maintaining the electrode potential by the redox potential of K2FeFe in a K2SO4 aqueous solution.

[0035] In one example, the method comprises the steps of preparing the slurry,

[0036] The slurry preparation step includes

[0037] Prussian blue analog particles,

[0038] Acetylene black, Ketjen black or multi-walled carbon nanotubes,

[0039] and the step of mixing polyvinylidene fluoride.

[0040] The Japanese patent application with application number 2022-134340 is the priority basis of the present application, and the disclosed contents of the application are incorporated herein.

[0041] Effects of the Invention

[0042] According to the all-solid-state potassium ion selective electrode and the manufacturing method thereof of the present invention, the stability of the potassium ion selective electrode can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 : The structure of the ion selective electrode 10 according to the first embodiment of the present invention.

[0044] Figure 2 :Used to form Figure 1 Part of the manufacturing step of the slurry in which the material 2 is embedded.

[0045] Figure 3 : Example of X-ray diffraction measurement results of Prussian blue analogs.

[0046] Figure 4 : Example of particle size measurement results for Prussian blue analogs.

[0047] Figure 5 : An example of a method for manufacturing the ion selective electrode 10.

[0048] Figure 6 : Example of constant current charge and discharge test results.

[0049] Figure 7 : Example of spontaneous potential measurement results.

[0050] Figure 8 : Figure 7 Reproducibility data of spontaneous potential measurements shown.

[0051] Fig. 9 : Example of long-term stability test results.

[0052] Fig.10 : Example of chronopotentiometry polarization test results.

[0053] Fig.11 : Example of Nyquist plot results in an AC impedance test.

[0054] Fig.12 : An example of the method of using the ion selective electrode 10.

[0055] Fig.13 : Structure of the electrode device 30 of the second embodiment.

[0056] Fig.14 : Fig.13 An example of how the electrode device 30 is used is shown. DETAILED DESCRIPTION

[0057] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings.

[0058] Implementation Method 1

[0059] Figure 1 The structure of the ion selective electrode 10 according to the first embodiment of the present invention is shown in FIG. The ion selective electrode 10 is an all-solid-state potassium ion selective electrode. Figure 1 (a) is a plane diagram, Figure 1 (b) is along Figure 1 Cross-sectional view along line BB in (a).

[0060] The ion selective electrode 10 includes an epoxy resin 5, a copper wire 4 disposed in the epoxy resin 5, a platinum electrode 3 (conductor) connected to the copper wire 4 and exposed on the surface of the epoxy resin 5, an embedding material 2 formed on the surface of the platinum electrode 3, and a potassium ion sensing membrane 1 covering the embedding material 2.

[0061] The epoxy resin 5 can be replaced by any insulating material, and the copper wire 4 and / or the platinum electrode 3 can be replaced by any conductor.

[0062] The embedded material 2 is a mixed material containing Prussian blue analog particles and conductive material particles. The Prussian blue analog particles have a structural formula of K x Fe[Fe(CN)6] y ·nH2O. wherein x is a number greater than or equal to 1.5 and less than or equal to 2, preferably close to 2. y is a number greater than 0 and less than or equal to 1, preferably close to 0. n is a number greater than or equal to 0.

[0063] The Prussian blue analog particles at least partially have a monoclinic crystal structure. The Prussian blue analog particles may also partially have a cubic crystal structure.

[0064] Hereinafter, an example of a method for manufacturing the ion selective electrode 10 is described. The manufacturing method includes the step of manufacturing a slurry for forming the intercalation material 2, and the ion selective electrode 10 is manufactured using the obtained slurry. x The substance FeFe is sometimes recorded as "K2FeFe", but this description does not mean that the value of x is 2, nor does it limit the range of x.

[0065] Figure 2 A part of the manufacturing steps for forming a slurry for embedding material 2 is shown. Figure 2 The steps shown are specifically steps for synthesizing the active substance contained in the slurry.

[0066] In order to synthesize K2FeFe as the active material contained in the slurry, 100 mL of ferrous chloride aqueous solution (4 mmolFe II Cl2) was added dropwise to 100 mL of potassium ferrocyanide aqueous solution containing divalent iron ions (4 mmol K4[Fe II (CN)6]·3H2O) while stirring (step S1). Such a solution preferably contains tripotassium citrate (1.0M) for K2FeFe particle size control and as a potassium source. The dropwise addition is performed, for example, at 0.5 mL / min in a nitrogen atmosphere. The stirring is performed, for example, with a stirring impeller at 300 rpm.

[0067] Thus, a white precipitate of a monoclinic Prussian blue analogue is obtained from the sample solution, thereby synthesizing K2FeFe. In addition, the method for synthesizing K2FeFe is not limited to Figure 2 As shown, those skilled in the art can design it appropriately.

[0068] Subsequently, the white precipitate is stirred (step S2). The stirring is performed, for example, using a stirring impeller at 300 rpm in a nitrogen atmosphere at room temperature for 15 hours. Thereafter, the white precipitate is filtered under a nitrogen atmosphere (step S3). Thereafter, the white precipitate is washed (step S4). The washing is performed, for example, with ion exchange water and ethanol under a nitrogen atmosphere. Since K2FeFe is a substance that is easily oxidized in the atmosphere, it is preferred that the white precipitate be washed with water and ethanol under a nitrogen atmosphere. Figure 2 Among the steps shown, steps S1 to S4 are carried out in a nitrogen atmosphere in the above-mentioned manner to prevent oxidation during the synthesis process.

[0069] Then, the white precipitate is dried (step S5). The drying is performed, for example, by vacuuming at 100°C for 24 hours.

[0070] The powder sample obtained in step S5 is exposed to the atmosphere for several days to obtain a blue powder of K2FeFe. The blue powder is a Prussian blue analog particle containing at least a portion of a cubic crystal structure, which serves as an active substance embedded in the material 2. The blue powder can be considered to be a dual-phase coexistence of Prussian blue and Prussian white.

[0071] Thus, the slurry manufacturing step includes a step of synthesizing Prussian blue analog particles at least partially containing a cubic crystal structure by oxidizing a monoclinic Prussian blue analog. In addition, although in the above example, room temperature oxidation is performed in the atmosphere by exposing it to the atmosphere for several days, the oxidation method is not limited thereto, and electrochemical oxidation may be performed, or other oxidation methods may be used. In addition, depending on the composition of K2FeFe, the oxidation step may be omitted.

[0072] Figure 3 Shown is an example of the results of X-ray diffraction measurements of a Prussian blue analog. Figure 3 (a) shows a comparative example when x=0.36 and y=0.67. Figure 3 (b) shows an example of this embodiment when x=1.69 and y=0.86. Figure 3 The “□” in the structural formula represents the [Fe(CN)6] defect.

[0073] Although x=1.69 in the first embodiment, the value of x is not limited to 1.69, and may be, for example, 1.65. It can be considered that as long as x is greater than or equal to 1.5 and less than or equal to 2, equivalent or homogeneous characteristics can be obtained. Similarly, although y=0.86 in the first embodiment, the value of y only needs to be greater than 0 and less than or equal to 1. In addition, as described above, x is preferably close to 2, and y is preferably close to 0.

[0074] In the drawings and the present specification, "cubic" is sometimes abbreviated as "c-", and "monoclinic" is sometimes abbreviated as "m-". For example, "c-KFeHCF" represents a cubic Prussian blue analog, and "m-KFeHCF" represents a monoclinic Prussian blue analog.

[0075] like Figure 3 As shown in (a), the composition with lower potassium content and more defects is a cubic phase. Figure 3 As shown in (b), the composition with higher potassium content and fewer defects is a monoclinic phase.

[0076] Figure 4 The figure shows an example of the particle size measurement result of the Prussian blue analog. The horizontal axis represents the particle size and the vertical axis represents the volume ratio. Compared with the m-KFeHCF of the first embodiment, the c-KFeHCF of the comparative example has a larger particle size because the particles are slightly more aggregated.

[0077] Figure 5 The example of manufacturing an ion selective electrode 10 with the active material synthesized in the above manner is shown. The method includes a slurry manufacturing step (step S11). The slurry manufacturing step includes the step of mixing the active material (Prussian blue analog particles) synthesized in the above manner, a conductive material, and a binder. The ratio of active material: conductive material: binder is, for example, 80:10:10 (weight percentage).

[0078] The conductive material is, for example, acetylene black, Ketjen black, or multi-walled carbon nanotubes. Figure 5 An example is acetylene black (AB). Figure 5 In the examples, the binder is polyvinylidene fluoride dispersed in N-methylpyrrolidone (NMP).

[0079] The slurry prepared according to the above method was dripped onto the platinum electrode 3 (see Figure 1 )(Step S12). The amount of dripping is, for example, 1 μL. Thereafter, the slurry is dried (Step S13). Drying is performed, for example, overnight at room temperature. In this way, a blended film is formed on the surface of the platinum electrode 3. It can be seen that the manufacturing method of embodiment 1 includes the step of forming a blended film on the surface of the platinum electrode 3 by providing the slurry on the platinum electrode 3 and drying the slurry.

[0080] In addition, as mentioned above, the slurry contains the structural formula K x Fe[Fe(CN)6] y · Prussian blue analog particles represented by nH2O. The Prussian blue analog particles at least partially have a monoclinic crystal structure, x is a number greater than or equal to 1.5 and less than or equal to 2, y is a number greater than 0 and less than or equal to 1, and n is a number greater than or equal to 0.

[0081] After that, the blended film is immersed in a 0.01M KCl aqueous solution (first potassium chloride aqueous solution) (step S14). The immersion is performed for 24 hours, for example. In this way, appropriate adjustment can be achieved so that the K + The embedded material 2 is evenly distributed on the surface of the platinum electrode 3 .

[0082] Subsequently, a potassium ion sensing membrane (K +-ISM) mother liquor (step S15). The amount of dropwise addition is, for example, 50 μL. The potassium ion sensing membrane mother liquor includes, for example, an ion carrier, a membrane matrix, a membrane solvent, and an anion repellent. The ion carrier is, for example, bis(benzo-15-crown-5), the membrane matrix is, for example, polyvinyl chloride (PVC), the membrane solvent is, for example, o-nitrophenyl octyl ether (o-NPOE), and the anion repellent is, for example, tetrakis(4-chlorophenyl) potassium borate (K-TCPB). Among them, tetrahydrofuran (THF) is used as the dispersion medium.

[0083] Afterwards, the potassium ion sensitive membrane mother solution is dried (step S16). The drying is performed, for example, overnight at room temperature. In this way, an ion responsive mother membrane is formed.

[0084] It can be seen that the manufacturing method of the first embodiment includes the steps of forming an ion-responsive mother membrane on the surface of the embedding material 2 by providing a potassium ion-sensitive membrane mother solution on the surface of the embedding material 2 and drying the potassium ion-sensitive membrane mother solution.

[0085] Thereafter, the ion-responsive mother membrane is immersed in a 0.01M KCl aqueous solution (second potassium chloride aqueous solution) (step S17). The immersion is performed for 24 hours, for example. In this way, appropriate adjustment can be achieved so that the potassium ion sensing membrane 1 is formed on the surface of the embedded material 2. In this way, a Figure 1 An ion selective electrode 10 is shown.

[0086] Next, the characteristics of the ion selective electrode 10 are described.

[0087] Figure 6 The following is an example of the results of a constant current charge and discharge test. The test was performed with the following structure:

[0088] System...SB9 (two-chamber three-electrode system)

[0089] Working electrode (ion selective electrode 10) ... PB (Prussian blue): KB (Ketjen black): PVdF (polyvinylidene fluoride) = 70: 20: 10 (weight percentage)

[0090] Counter electrode...AC:KB:PTFE (polytetrafluoroethylene) = 80:10:10 (weight percentage)

[0091] Reference electrode...Ag / AgCl (saturated KCl)

[0092] Electrolyte: 0.5M K2SO4 aqueous solution

[0093] Diaphragm...Glass fiber filter

[0094] Current density...1C(156mAg -1 )

[0095] Voltage range: -0.25V to 0.50V (compared with Ag / AgCl)

[0096] Figure 6 In the figure, the horizontal axis represents the charge and discharge amount, and the vertical axis represents the potential. Figure 6 (a) shows the result when using the comparative example electrode, wherein the structural formula K x Fe[Fe(CN)6] y ·x in nH2O is less than 1.5. Hereinafter, this composition is sometimes referred to as "c-KFeHCF". Figure 6 As shown in (a), the potential of the comparative example electrode changes in an inclined manner, so it is considered to be a single-phase reaction.

[0097] Figure 6 (b) shows the result when the electrode of the first embodiment is used, wherein the structural formula K x Fe[Fe(CN)6] y ·x in nH2O is greater than or equal to 1.5. Hereinafter, this composition is sometimes referred to as "m-KFeHCF". Figure 6 As shown in (b), in the first embodiment, the electrode obtains a stable potential platform, so it is considered to be a two-phase reaction.

[0098] Figure 7 The following is an example of the spontaneous potential measurement results. In order to study the response of the obtained electrode to potassium ions, the spontaneous potential was measured in aqueous solutions with different potassium ion concentrations. The horizontal axis represents the logarithm of the potassium ion concentration, and the vertical axis represents the potential. In addition, E 0 It represents the intercept of the calibration curve when the concentration is 0.01.

[0099] There is no significant difference in sensitivity and detection limit between the electrode using the comparative example c-KFeHCF and the electrode using the m-KFeHCF of the first embodiment. However, the absolute value of the potential of the first embodiment is lower. The reason for this is considered to be that the potassium content of the crystals in the first embodiment is higher, and the potassium ion activity is greater, which reduces the membrane potential.

[0100] Figure 8 Shown Figure 7 The reproducibility data of the spontaneous potential measurement are shown in FIG. 3. Three electrodes with the same structure (respectively indicated as #1 to #3) were made and the spontaneous potential measurements were performed on them.

[0101] Fig. 9 An example of a long-term stability test result is shown below. The test is performed with the following configuration and measures the change in potential of the working electrode relative to the reference electrode.

[0102] Working electrode……Potassium ion selective electrode

[0103] Reference electrode...Ag / AgCl (saturated KCl)

[0104] Measuring solution...10 -2 M KCl aqueous solution

[0105] Measuring temperature... Room temperature

[0106] Fig. 9 In the figure, the horizontal axis represents time (days) and the vertical axis represents potential. Fig. 9 (a) shows the measurement results of the comparative example and the first embodiment. The long-term stability of the electrode using the comparative example c-KFeHCF is the worst. The reason for this is considered to be that the potential curve has the following characteristics: Figure 6 The reason is that the potential changes greatly when the composition changes due to the inclined shape shown in (a).

[0107] As an electrode using m-KFeHCF of the first embodiment, an electrode for oxidizing a Prussian blue analogue at room temperature in the atmosphere in the slurry manufacturing step and an electrode for electrochemically oxidizing a Prussian blue analogue in the slurry manufacturing step were prepared and tested respectively. Among them, the electrode using electrochemical oxidation was placed in a K2SO4 aqueous solution to maintain the redox potential of K2FeFe. By maintaining the potential in this way, the potassium content in the crystal can be adjusted, thereby further improving the long-term stability.

[0108] like Figure 6 As shown in (b), the potential curve of the electrode oxidized at room temperature in the atmosphere has a platform, so when the composition changes, the potential changes less and the stability is higher. Figure 6 As shown in (b), the platform characteristics of the potential curve of the electrode using electrochemical oxidation are more prominent and have the highest long-term stability.

[0109] Fig. 9 (b) shows the reproducibility data of the electrode oxidized at room temperature in the atmosphere in Embodiment 1. Three electrodes with the same structure were made and the long-term stability tests were performed on them respectively.

[0110] like Fig. 9 As shown in (a), the comparative example electrode showed a potential change of about 20 mV on the sixth day. Fig. 9 (a) and Fig. 9 As shown in (b), the electrode in Embodiment 1 only exhibits a potential change of less than or equal to about 10 mV on the sixth day.

[0111] It can be seen that the all-solid-state potassium ion selective electrode of the first embodiment uses K2FeFe, which is a two-phase coexistence of Prussian blue and Prussian white, as an active material to suppress the potential change to less than or equal to about 10 mV, thereby improving the long-term stability of the electrode.

[0112] Fig.10 Shown is an example of the results of a chronopotentiometry polarization test. The test was performed with the following setup.

[0113] Working electrode……Potassium ion selective electrode

[0114] Counter electrode……Platinum wire

[0115] Reference electrode...Ag / AgCl (saturated KCl)

[0116] Electrolyte……10 -2 M KCl aqueous solution

[0117] Applied current... ±1nA

[0118] Measuring temperature... Room temperature

[0119] Fig.10 In FIG. 1 , the horizontal axis represents time and the vertical axis represents potential. At 300 s, the current direction is reversed. The results of the comparative example and the first embodiment are almost the same.

[0120] Fig.11 Shown is an example of a Nyquist plot result from an AC impedance test. Fig.11 The horizontal axis in represents the real part of the impedance, and the vertical axis represents the imaginary part. This test is performed with the following structure.

[0121] Working electrode……Potassium ion selective electrode

[0122] Counter electrode……Platinum wire

[0123] Reference electrode...Ag / AgCl (saturated KCl)

[0124] Electrolyte……10 -2 M KCl aqueous solution

[0125] Amplitude...100mV

[0126] Frequency: 100kHz~10mHz

[0127] Measuring temperature... Room temperature

[0128] The results of the comparative example and the first embodiment are almost the same, but the resistance of the first embodiment is slightly lower. The reason for this is considered to be as follows Figure 4 This is because the particle size shown is smaller.

[0129] As described above, the stability of the potassium ion selective electrode can be further improved by the all-solid-state potassium ion selective electrode and the manufacturing method thereof according to the first embodiment.

[0130] Fig.12The figure shows an example of the method of using the ion selective electrode 10. The ion selective electrode 10 and the reference electrode 11 are immersed in the test liquid 12, and the ion selective electrode 10 and the reference electrode 11 are electrically connected through a voltage measuring device 13. The voltage measuring device 13 measures the potential difference between the ion selective electrode 10 and the reference electrode 11, and outputs a signal representing the potential difference. Since the measured potential difference changes with the potassium ion concentration contained in the test liquid 12, the potassium ion concentration can be calculated based on the potential difference.

[0131] Implementation Method 2

[0132] Embodiment 2 changes the specific structure of the ion selective electrode based on Embodiment 1. The description of the parts common to Embodiment 1 may be omitted below.

[0133] Fig.13 The structure of the electrode device 30 of the second embodiment is shown. The electrode device 30 includes a substrate 21, an ion selective electrode 20 and a reference electrode 11. The substrate 21 is made of, for example, aluminum oxide. The ion selective electrode 20 and the reference electrode 11 are formed on the substrate 21.

[0134] The ion selective electrode 20 is a fully solid potassium ion selective electrode and has the same structure as the ion selective electrode 10 of the first embodiment (the difference is that the insulating material part is replaced by the substrate 21 instead of the epoxy resin 5). In addition, the ion selective electrode 20 can be manufactured by the same manufacturing method as the ion selective electrode 10 of the first embodiment.

[0135] A pair of connection structures 22 are formed on the substrate 21. The pair of connection structures 22 are connected to the ion selective electrode 20 and the reference electrode 11 respectively through wires 23. Part of the surface of the substrate 21, including the area where the wires 23 are formed, is covered with a protective film 24 (a transparent area shown by a dotted line) formed of an insulating material such as epoxy resin. The ion selective electrode 20 and the reference electrode 11 are not covered by the protective film 24, and the connection structures 22 are also not (at least partially) covered by the protective film 24.

[0136] Fig.14 The figure shows an example of the method of using the electrode device 30. The ion selective electrode 20 and the reference electrode 11 are immersed in the test liquid 12, and the ion selective electrode 20 and the reference electrode 11 are electrically connected through the voltage measuring device 13. The voltage measuring device 13 measures the potential difference between the ion selective electrode 20 and the reference electrode 11, and outputs a signal representing the potential difference. Since the measured potential difference changes with the potassium ion concentration contained in the test liquid 12, the potassium ion concentration can be calculated based on the potential difference.

[0137] Since the all-solid-state potassium ion selective electrode of the second embodiment has the same structure as that of the first embodiment and is manufactured by the same manufacturing method, similar to the first embodiment, the stability of the potassium ion selective electrode can be further improved.

[0138] Reference numerals

[0139] 1...Potassium ion sensing membrane

[0140] 2…Embedding Materials

[0141] 3……Platinum electrode (conductor)

[0142] 4...Copper wire

[0143] 5. Epoxy resin

[0144] 10……Ion selective electrode (all-solid-state potassium ion selective electrode)

[0145] 11……Reference electrode

[0146] 12……Test liquid

[0147] 13... Voltage measuring device

[0148] 20...Ion selective electrode (all-solid-state potassium ion selective electrode)

[0149] 21...base

[0150] 22……Connection structure

[0151] 23...Wire

[0152] 24...Protective film

[0153] 30...Electrode device

[0154] All publications, patents, and patent applications cited in this specification are fully incorporated into this specification by reference.

Claims

1. An all-solid-state potassium ion selective electrode, characterized in that: include: conductor; an embedding material formed on the surface of the conductor; as well as a potassium ion sensing membrane covering the embedding material, Wherein, the embedding material is a mixed material containing Prussian blue analog particles and conductive material particles, The Prussian blue analog particles have a structural formula K x Fe[Fe(CN)6] y nH2O means, The Prussian blue analog particles at least partially have a monoclinic crystal structure, x is a number greater than or equal to 1.5 and less than or equal to 2, y is a number greater than 0 and less than or equal to 1, and n is a number greater than or equal to 0.

2. A method for manufacturing an all-solid-state potassium ion selective electrode, characterized in that: The all-solid-state potassium ion selective electrode comprises: conductor; an embedding material formed on a surface of the conductor; and a potassium ion sensing membrane covering the embedding material, Wherein, the embedding material is a mixed material containing Prussian blue analog particles and conductive material particles, The Prussian blue analog particles have a structural formula K x Fe[Fe(CN)6] y nH2O means, The Prussian blue analog particles at least partially have a monoclinic crystal structure, x is a number greater than or equal to 1.5 and less than or equal to 2, y is a number greater than 0 and less than or equal to 1, n is a number greater than or equal to 0, The method comprises the following steps: providing a slurry on a conductor, and drying the slurry to form a blended film on a surface of the conductor; The blended membrane is immersed in a first potassium chloride aqueous solution so that K + uniformly distributed in the Prussian blue analog to form an embedded material on the surface of the conductor; providing a potassium ion sensing membrane mother solution on the surface of the embedding material, and drying the potassium ion sensing membrane mother solution to form an ion responsive mother membrane on the surface of the embedding material; and The potassium ion sensing membrane is formed on the surface of the embedding material by immersing the ion responsive mother membrane in a second potassium chloride aqueous solution.

3. The method according to claim 2, characterized in that The method comprises the steps of preparing the slurry, The step of preparing the slurry includes the step of synthesizing Prussian blue analog particles at least partially including a cubic crystal structure by oxidizing a monoclinic Prussian blue analog.

4. The method according to claim 2 or 3, characterized in that After the step of forming the potassium ion sensitive membrane, the method includes the step of maintaining the electrode potential by the redox potential of K2FeFe in a K2SO4 aqueous solution.

5. The method according to claim 2 or 3, characterized in that: The method comprises the steps of preparing the slurry, The step of making the slurry comprises the step of mixing the following substances: Prussian blue analog particles, Acetylene black, Ketjen black or multi-walled carbon nanotubes, and Polyvinylidene fluoride.

Citation Information

Patent Citations

  • Total solid type ion-selective electrode and method for manufacturing total solid type ion-selective electrode

    JP2020046364A

  • Peripheral apparatus, monitoring system, monitoring method, and program

    JP2022134340A

Cited By

  • Metal-doped Prussian blue derivative as well as preparation method and application thereof

    CN120440913A